Annotation of Hox cluster and Hox cofactor genes in the Asian citrus psyllid, Diaphorina citri, reveals novel features - Teresa D. Shippy; Prashant S. Hosmani; Mirella Flores-Gonzalez; Lukas A. Mueller; Wayne B. Hunter; Susan J. Brown; Tom D’Elia; Surya Saha (GigaByte, 2022)
Hox genes and their cofactors are essential developmental genes specifying regional identity in animals. Hox genes have a conserved arrangement in clusters in the same order in which they specify identity along the anterior–posterior axis. A few insect species have breaks in the cluster, but these are exceptions. We annotated the 10 Hox genes of the Asian citrus psyllid Diaphorina citri, and found a split in its Hox cluster between the Deformed and Sex combs reduced genes – the first time a break at this position has been observed in an insect Hox cluster. We also annotated D. citri orthologs of the Hox cofactor genes homothorax, PKNOX and extradenticle and found an additional copy of extradenticle in D. citri that appears to be a retrogene. Expression data and sequence conservation suggest that the extradenticle retrogene may have retained the original extradenticle function and allowed divergence of the parental extradenticle gene.